Poesia, imaginação poética e memória em Virgínia Vendramini - Anschau, Lucilaine Tavares da Silva (2016)
This research aims is to investigate the work of artist Virginia Vendramini (1945) in order to analyze images of childhood retained in memory and poetically rebuilt in an attempt to bring them back to the present. Poetry is the art of breaking, in that it allows man to break up with a common perception of reality which necessarily leads to the study of poetic imagery, imagination and memory articulating thoughts of Gaston Bachelard the phenomenological method as a path to understanding the essence of be the creation of the poet. The poetic images allow man to be recognized in its uniqueness and give meaning to your life. Imagination has a central place in human existence with regard to the relationship of the human being with oneself, others and the significance of their world. The memory rescues significant images of ancient times, especially in childhood. The practice of childhood recollection is essential to poetic creation Virgínia Vendramini trying to relate to children's poetic images as a way to recreate and relive reality. In this study, a brief analysis of the poems that address the childhood theme is complemented by images of art created by Virginia Vendramini from the weaving technique and ceramic sculpture, covering the categories of analysis: a) poetic recollection; b) resonance and repercussions and, c) archetype and individuation. The dissertation consists of three chapters, the first are elucidated the concepts poetic imagery, imagination, memory and reverie and presentation of the life and artistic production Virgínia Vendramini. In the second chapter, lies the imaginary in the light of the phenomenological method of Bachelard, under the focus of poetic creation, establishing a parallel between poetry, experiences and memories and poetic reveries facing childhood. The thematic pairs: poetry / childhood and experience / memory are covered in the third chapter. The theoretical assumptions anchored in authors such as Gaston Bachelard (1993, 2009), Walter Benjamin (1989; 1994a; 1994b), Gilbert Durand (1998), Carl Jung (1987), Octavio Paz (2012), Alfredo Bosi (1977), João Carlos Tedesco (2004) and Ana Maria Lisboa de Mello (2002)